Estimating the free gas content in Baltic Sea sediments using compressional wave velocity from marine seismic data. Issue 12 (5th December 2014) - Tóth, Zsuzsanna; Spiess, Volkhard; Mogollón, José M.; Jensen, Jørn Bo
Abstract A 2‐D high‐resolution velocity field was obtained from marine seismic data to quantify free gas content in shallow muddy sediments at in situ pressure and temperature. The velocities were acquired applying Migration Velocity Analysis on prestack time‐migrated data. Compressional wave velocities are highly sensitive to free gas as very small amounts of gas can cause a significant decrease in the medium velocity. The analyzed profile crosses a depression filled with organic‐rich Holocene mud in the Bornholm Basin, Baltic Sea. The interval velocity field reveals two low‐velocity patches, which extend from the reversed polarity reflections marking the top of the gassy sediment layer down to the base of the Holocene mud. Average interval velocities within the gassy mud are lower than the seafloor migration velocity by up to ∼500 m/s. This decrease, using a geoacoustic model, is caused by an average 0.046% gas volume fraction. The interval velocities in individual cells of the velocity field are reduced to ∼200 m/s predicting up to 3.4% gas content. The velocity field is limited in resolution due to velocity determination at and between reflections; however, together with the stratigraphic interpretation, geological units containing free gas could be identified. Shallow gas occurs vertically throughout most of the Holocene mud in the gassy area. Comparison with biogeochemical studies at other Baltic Sea sites suggests that the distribution of free gas is likely to be patchy in the sediment, but the gas concentration may peak below the sulfate‐methane transition zone and gradually decrease below.